The Role of Neutrophils and Neutrophil Elastase in Pneumococcal Pneumonia - Domon, Hisanori; Terao, Yutaka (Frontiers in Cellular and Infection Microbiology, 2021)
Streptococcus pneumoniae, also known as pneumococcus, is a Gram-positive diplococcus and a major human pathogen. This bacterium is a leading cause of bacterial pneumonia, otitis media, meningitis, and septicemia, and is a major cause of morbidity and mortality worldwide. To date, studies on S. pneumoniae have mainly focused on the role of its virulence factors including toxins, cell surface proteins, and capsules. However, accumulating evidence indicates that in addition to these studies, knowledge of host factors and host-pathogen interactions is essential for understanding the pathogenesis of pneumococcal diseases. Recent studies have demonstrated that neutrophil accumulation, which is generally considered to play a critical role in host defense during bacterial infections, can significantly contribute to lung injury and immune subversion, leading to pneumococcal invasion of the bloodstream. Here, we review bacterial and host factors, focusing on the role of neutrophils and their elastase, which contribute to the progression of pneumococcal pneumonia.